A diversified exploration of beef cattle genetics: miRNA and beef bull fertility in beef and dairy female populations - Shaffer, William Ryan (My University, 2025)
This dissertation represents a conglomeration of many different topics in the field of animal breeding. Topics explored include analysis of micro ribonucleic acid (miRNA) expression as it relates to quantitative traits, genetic analysis of sire conception rate (SCR) in dairy cow and beef heifer populations, and the genetic correlation between SCR in both populations. The objectives of the miRNA project were to elucidate differentially expressed (DE) miRNA resulting from changes in phenotypic expression of average daily gain (ADG), daily mean dry matter intake (dmDMI), and daily mean water intake (dmWI), validate these miRNA with DE in their predicted gene targets, and to gain insight on biological functions of predicted gene targets. We found that factorizing the three traits with k-means clustering or classifying observations greater or less than 1 standard deviation from the mean as high or low, respectively, yielded the most power to discover DE miRNA and mRNA. While multiple predicted gene targets were validated for several significantly DE miRNA, no gene ontology or gene pathways were significantly associated with the validated gene targets. Almost all gene targets were associated with lipid metabolism and lipid deposition in previous literature, which may be related to dmDMI and ADG. Exploration of biochemically connected traits to further improve power may be warranted. The objectives of the SCR project were to estimate the heritability of beef SCR in a dairy cow and beef heifer population as well as to estimate the genetic correlation between the two populations. The estimated heritability of SCR in the dairy cow and beef heifer population was exceedingly low at 1.74% (95% confidence interval 1.51% to 1.95%) and 2.10% (1.66% to 2.62%), respectively, but the 95% confidence intervals provided evidence for a weakly heritable component. The genetic correlation between SCR in the two populations was estimated at 0.02 (-0.13 to 0.19). This indicated that beef SCR records from dairy cows and beef heifers should not be utilized in the prediction of one another. Finally, exploration of other methods to improve male fertility may yield more genetic progress than selection on SCR given the low heritability and problems associated with data collection.
Keywords: Sire conception rate; miRNA; Differential expression; Dry matter intake; Water intake; Male fertility